Quantitative Assessment of Clinician Assistance During Dynamic Rehabilitation Using Force Sensitive Resistors - Linde, Margaux B.; Thoreson, Andrew R.; Lopez, Cesar; Gill, Megan L.; Veith, Daniel D.; Hale, Rena F.; Calvert, Jonathan S.; Grahn, Peter J.; Fautsch, Kalli J.; Sayenko, Dimitry G.; Zhao, Kristin D. (Frontiers in Rehabilitation Sciences, 2021)
Background Neuromodulation using epidural electrical stimulation (EES) has shown functional restoration in humans with chronic spinal cord injury (SCI). EES during body weight supported treadmill training (BWSTT) enhanced stepping performance in clinical trial participants with paraplegia. Unfortunately, tools are lacking in availability to quantify clinician assistance during BWSTT with and without EES. Force sensitive resistors (FSRs) have previously quantified clinician assistance during static standing; however, dynamic tasks have not been addressed. Objective Determine the validity of FSRs in measurements of force and duration to quantify clinician assistance and participant progression during BWSTT with EES in participants with SCI. Design A feasibility study to determine the effectiveness of EES to restore function in individuals with SCI. Methods Two male participants with chronic SCI were enrolled in a pilot phase clinical trial. Following implantation of an EES system in the lumbosacral spinal cord, both participants underwent 18 months of BWSTT with EES. At monthly intervals, FSRs were positioned on participants’ knees to quantity forces applied by clinicians to achieve appropriate mechanics of stepping during BWSTT. FSRs were validated on the benchtop using a leg model instrumented with a multiaxial load cell as the gold standard. Outcomes included clinician-applied force duration measured by FSR sensors and changes in applied forces indicating progression over the course of rehabilitation. Results FSR validation revealed a proportional bias in their output. Loading required for maximal assist training exceeded the active range of the FSRs but were capable of capturing changes in clinician assist levels. FSRs were also temporally responsive which increased utility for accurately assessing training contact time. FSRs readings were able to capture independent stance for both participants at month 18. There was minimal to no applied force bilaterally for participant 1 and unilaterally for participant 2. Conclusion Clinician assistance applied at the knees as measured through FSRs during dynamic rehabilitation and EES (both on and off) effectively detected point of contact and duration of forces, however, lacks accuracy of magnitude assessment. Reduced contact time as measured through FSRs related to increased stance duration which objectively identified independence in stepping during EES-enabled BWSTT following SCI.